Design and demonstration of an intracortical probe technology with tunable modulus. Issue 1 (21st September 2016) - Simon, Dustin M.; Charkhkar, Hamid; St. John, Conan; Rajendran, Sakthi; Kang, Tong; Reit, Radu; Arreaga‐Salas, David; McHail, Daniel G.; Knaack, Gretchen L.; Sloan, Andrew; Grasse, Dane; Dumas, Theodore C.; et al.
Abstract: Intracortical probe technology, consisting of arrays of microelectrodes, offers a means of recording the bioelectrical activity from neural tissue. A major limitation of existing intracortical probe technology pertains to limited lifetime of 6 months to a year of recording after implantation. A major contributor to device failure is widely believed to be the interfacial mechanical mismatch of conventional stiff intracortical devices and the surrounding brain tissue. We describe the design, development, and demonstration of a novel functional intracortical probe technology that has a tunable Young's modulus from ∼2 GPa to ∼50 MPa. This technology leverages advances in dynamically softening materials, specifically thiol‐ene/acrylate thermoset polymers, which exhibit minimal swelling of < 3% weight upon softening in vitro . We demonstrate that a shape memory polymer‐based multichannel intracortical probe can be fabricated, that the mechanical properties are stable for at least 2 months and that the device is capable of single unit recordings for durations up to 77 days in vivo . This novel technology, which is amenable to processes suitable for manufacturing via standard semiconductor fabrication techniques, offers the capability of softening in vivo to reduce the tissue‐device modulus mismatch to ultimately improve long term viability of neural recordings. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 159–168, 2017.